Pengaruh Pelatihan Komunikasi Efektif terhadap Motivasi Kerja Widyaiswara Balai Besar Pengembangan Penjaminan Mutu Pendidikan Vokasi Seni dan Budaya Yogyakarta - Ali Imron; Alimatus Sahrah (Jurnal Psikologi, 2023)
This study discusses the lack of work motivation due to continuous work demands in BBPPMPV widyaiswara Arts and Culture. This study to determine the impact of effective communication training on employee motivation BBPPMPV widyaiswara Arts and Culture. This research is an experimental research with experimental group design and control group. The subjects are 20 employees with moderate and low of motivation and effective communication than devided in to two groups, 10 people as an experimental group and 10 people as a control group. The techniques used to collect data is the scale of work motivation.Data analysis using Wilcoxon, U-Mann Whitney and Gain Score statistics. The results show the influence of effective communication training on employee motivation BBPPMPV widyaiswara Arts and Culture. Employees who are trained in effective communication have increased work motivation compared to non-trained employees. The results of data analysis showed that the group of employees who were given effective communication training had a higher score than the group of employees who were not trained with a value of Z = -3,178, (p <0.05).